MORPHOLOGICAL IDENTIFICATION OF ANGIOSPERM FLOWERS AS A LEARNING RESOURCE REFERENCE FOR THE COURSE ON PLANT DEVELOPMENT STRUCTURE - Dwi Swastanti Ridianingsih; Rima Suwistika (BIOCHEPHY: Journal of Science Education, 2025)
Angiosperm flowers at Bakti Indonesia University are diverse, and their use as learning resources is not yet optimal. The purpose of this study was to determine the diversity of angiosperm flowers at Bakti Indonesia University and their morphological structure. The type of research is descriptive qualitative with exploratory methods and descriptive data analysis approaches. Data collection techniques used documentation and then identified the morphological structure. The research location is Bakti Indonesia University. The results of the study found 7 families of angiosperm flowers, including the Rubiaceae family, the Euphorbiaceae family, the Nyctaginaceae family, the Acanthaceae family, the Caricaceae family, the Apocynaceae family, and the Solanaceae family. The conclusion of the results of this flower diversity can be used as a learning resource for students.